A Line in the Sand - Lacy, Al; Lacy, JoAnna (Colorado Springs, Colo. : Multnomah Books, 2007)
Alan and Adam Kane arrive in Texas in 1835 and join up with Jim Bowie, Davy Crockett, and other Texans as they join forces against Mexico's General Santa Anna, with plans to station themselves in the Texan fort known as the Alamo.
Keywords: Texas -- Fiction -- History